Impact of Anthropometric Parameters on Pressure Variables for Determining Comfort and Safety of Automotive Seat: A Systematic Review - Nabilah Sabri; Nor Kamaliana Khamis; Mohd Faizal Mat Tahir; Jailani Besar; Dzuraidah Abd Wahab (Tehran University of Medical Sciences, 2022)
Background: A good quality of seating comfort requires integration of capabilities and limitations of the human body and the occupant's preferred posture in different seating environments and tasks. This study provides a systematic and comprehensive review of past research related to the correlation between anthropometric parameter to seat pressure variables to determine the impact on comfort and safety in seat design. Methods: This systematic review consisted of PRISMA flow diagram guidelines searched in Web of Science, Scopus, Sciencedirect and Google Scholar from 2009 till January 2020 related to keyword lists. Results: As a result, 26 articles which addressed the correlation between anthropometric parameters and pressure variables were selected. Body mass index and weight were the most influence anthropometric parameter towards the pressure variables. In addition, almost all studies showed that there were medium to strong correlation between the lower body parts and the pressure variables, with R as above 0.5. Conclusion: Comfort and safety depend on the design and ergonomics of the seat to maintain the body posture under complex roads, driving conditions and changing environment. In essence, seat and geometry functions help to reduce fatigue level and improve comfort, safety and health among drivers based on user, task and environment of driving activities.